2007
DOI: 10.1093/jpepsy/jsm003
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Parental Report of Sleep Behaviors Following Moderate or Severe Pediatric Traumatic Brain Injury

Abstract: Children who sustain severe TBI are at elevated risk for post-injury sleep problems. Because sleep problems may result in daytime impairments and family distress, additional clinical and research attention is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…Although the clinical significance of the findings is uncertain, given the modest size of the group differences, the results are consistent with previous research documenting increased sleep problems after pediatric TBI up to 3 years postinjury. 6,9,10 The relationship of sleep problems to TBI severity was not entirely clear, however, and further research is needed to determine the pathophysiological mechanisms that account for increased sleep disturbance after TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clinical significance of the findings is uncertain, given the modest size of the group differences, the results are consistent with previous research documenting increased sleep problems after pediatric TBI up to 3 years postinjury. 6,9,10 The relationship of sleep problems to TBI severity was not entirely clear, however, and further research is needed to determine the pathophysiological mechanisms that account for increased sleep disturbance after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown more sleep disturbance in children with TBI than in healthy children or in those with orthopedic injuries (OIs). [6][7][8][9][10] Sleep problems have been demonstrated in children with both mild (mTBI) and more severe TBI (sTBI), persisting up to 3 years postinjury, as measured by self-and parent ratings as well as by objective sleep-monitoring measures (e.g., actigraphy and polysomnography [PSG]). 7,10 However, not all studies have found sleep problems to be associated with TBI or to be related to injury severity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of sleep disturbances in pediatric patients following TBI demonstrated that most studies focused on adolescents and used subjective measures to evaluate symptoms (Gagner et al 2015;Hung et al 2014;Beebe et al 2007). However, sleep disturbances were common post-injury and included excessive daytime sleepiness, increased sleep latency and circadian rhythm disruption, though the latter was not as common (Gagner et al 2015).…”
Section: Special Considerations In the Pediatric Populationmentioning
confidence: 99%
“…The CBCL is designed for use with children ages 6 to 18 years. Subsets of items from the CBCL have also been analyzed to characterize sleep problems (Beebe et al, 2007), post-traumatic stress symptoms (Gragert et al, 2010), and ADHD . Administration time for this subscale is *10 min, and Spanish translations are available.…”
Section: Psychiatric and Psychological Functioningmentioning
confidence: 99%